Microfiber platform for oligodendrocyte myelination - Ong, William (Nanyang Technological University, 2020)
Injuries or disorders in the central nervous system disrupt crucial sensory and motor functions. This critical system has limited regenerative capability, often contributes directly to permanent disabilities in afflicted adults. Limited regenerative capability is likely a result of the disruption of the intrinsic nervous system environment following injuries and diseases. The lack of treatment options stems from our lack of understanding of nervous tissue regeneration and alteration in nerve cellular microenvironment. As such, recent studies focused on unveiling the cellular biology of nervous system, zooming in on events following distress to uncover specific mechanisms that impede tissue regrowth and functional recovery. In this thesis, we developed platforms to help enhance our understanding of the nervous system with clever engineering. Specifically, we developed an artificial fiber-based platform for oligodendrocyte myelination. Our systems deliver simple solutions to study the complex process of multilamellar wrapping by oligodendrocyte, which is crucial in maintaining the functions of the central nervous system. We model intrinsic axons and the nervous system microenvironment with suitable materials and structures, to study the mechanobiology of oligodendrocyte myelination. We first optimized the oligodendrocyte myelin-artificial axons culture in vitro to evaluate the feasibility of attaining physiologically relevant myelination with electrospun fibers. With appropriate biophysical and chemical cues, oligodendrocytes produced robust multilamellar myelin sheaths surrounding artificial axons engineered with synthetic polymers. Morphologically, we observed concentric wrapping around our electrospun fibers, mimicking closely the physiological central nervous system myelination. We developed a drug/gene screening platform designed as a quick, simple and cheap alternative to animal testing. Using molecules known to promote oligodendrocyte myelination, we showed that our physiologically relevant system produced readouts similar to animal experiments, thereby highlighting it as an efficient platform to screen potential therapeutics targeting remyelination. To further enhance the utility of our artificial axons drug/gene screening platform, we evaluated the efficacy of incorporating engineered mesoporous silica nanoparticles in our system for neuronal cells. We achieved highly efficient uptake of RNA by all major neuronal and glia cells through optimization of particles to RNA ratio. With the particles-RNA complex, we performed gene silencing experiments to highlight the efficacy of incorporated nanoparticles. In comparison to commercial transfection reagents, our engineered particles displayed similar silencing efficacy on our screening platform. We further developed our artificial axons platform to study the mechanobiology of oligodendrocyte myelination. Using three-point bending theory, we established a tunable structural stiffness platform, which decouples stiffness from other biophysical cues, to investigate the effect of pathological stiffening of microenvironment on oligodendrocyte myelination. We demonstrated that increasing structural stiffness promotes oligodendrocyte precursor differentiation, which was validated with conventional two-dimensional tunable stiffness hydrogels. Moreover, for the first time, we demonstrated with our artificial axonbased tunable stiffness, that an increase in structural stiffness impedes oligodendrocyte myelination. We investigated the role of YAP signaling in the mechanotransduction of oligodendrocyte and observed translocation of YAP into oligodendrocyte nucleus in high stiffness microenvironment. When examined the crucial actin turnover process required for myelination, we observed significantly higher F-actin ratio in high stiffness microenvironment, suggesting an obstructed actin disassembly process. We extended our tunable structural stiffness platform to study the effect of intrinsic axonal stiffness on oligodendrocyte myelination. By controlling the crystallinity of artificial axons, we demonstrated tunable intrinsic stiffness in individual fibers. Similar to tunable structural stiffness platform, our intrinsic stiffness platform decouples the changes in intrinsic stiffness from other biophysical parameters that could influence myelination. Using this novel platform, we demonstrated that high intrinsic stiffness of individual artificial axons hinders oligodendrocyte myelination. Taken together, this thesis advanced the utility of an electrospun polymer-based artificial axons platform for oligodendrocyte myelination. Crucially, platforms introduced in this thesis help accelerate the drug discovery process for myelin degenerative diseases and improve our understanding of myelination.